O MUNDO DO FUTEBOL NAS CRÔNICAS DE NELSON RODRIGUES - Silva, Marcelino Rodrigues da (Em Tese, 1998)
This work aims to discuss the process of production of Brazilian soccer mythology , analyzing Nelson Rodrigues soccer chronicles to show how they articulate meanings that are part of the collective repertory through which soccer is interpreted in Brazil.